Nigeria’s Rentier State and the Praxis of Underdevelopment and Insecurity - Manu, Yusuf Abdullahi; Lawan, Mohammed; Mohammed, Yunusa; Musa, Auwalu (Kashere Journal of Politics and International Relations, 2023)
Oil shows an unbearable contradiction to Nigeria through huge wealth and means of patronage for Nigeria as a rentier State and the transnational oil companies while Nigerians are left in the gallows of poverty and misery, stumbling in condition of despondency and hopelessness. This study explored the challenges to Nigeria’s developmental drive as occasioned by the rentier nature of the Nigeria’s economy. Oil has become the singular major source of foreign exchange earnings. The mono economy created a condition that hampers Nigeria’s ability to effectively diversify the nation’s economy and provide the desired developmental opportunities needed for its teeming populace. The paper utilised secondary sources of data collection and documentary analysis as its methodology using content analysis. Using rentier state theory as an explanatory analytical means, the paper established that the implications of mono produce state and economy bolstered selfishness among the populace in addition to other establishments; and nurtured dependency on cheaper pecuniary advantages thus, rendering the state unreasonably centralised, unresponsive to its citizens, and corruption personified. It concluded that Nigeria’s over dependence on revenue from oil if not properly addressed, will cause sharp socioeconomic downturns, political instability and underdevelopment.